2016
DOI: 10.1080/01616412.2016.1187830
|View full text |Cite
|
Sign up to set email alerts
|

Association of CT perfusion and postoperative cognitive dysfunction after off-pump coronary artery bypass grafting

Abstract: Abnormal CT perfusion is a significant risk factor for postoperative cognitive dysfunction, and has the most impact on visuospatial/executive and naming functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Mean arterial pressure has been shown to need to be maintained between 80 and 90 mmHg during CPB, without intraoperative pressure dropping more than 32 mmHg [51], because brain hypoperfusion may lead to POCD [52]. Similarly, surgical manipulation during beating-heart surgery may reduce cardiac output; therefore, decreasing systemic blood pressure might reduce the brain perfusion index [12,53]. Although hypothermia is associated with decreased oxygen consumption and carbon dioxide production, studies have shown opposite effects of spontaneous hypothermia (32–35°C) during surgical procedures on cognitive functions [54,55], probably because of the rewarming effect after weaning off CPB [35].…”
Section: Surgery Perfusion-related Risk Factorsmentioning
confidence: 99%
“…Mean arterial pressure has been shown to need to be maintained between 80 and 90 mmHg during CPB, without intraoperative pressure dropping more than 32 mmHg [51], because brain hypoperfusion may lead to POCD [52]. Similarly, surgical manipulation during beating-heart surgery may reduce cardiac output; therefore, decreasing systemic blood pressure might reduce the brain perfusion index [12,53]. Although hypothermia is associated with decreased oxygen consumption and carbon dioxide production, studies have shown opposite effects of spontaneous hypothermia (32–35°C) during surgical procedures on cognitive functions [54,55], probably because of the rewarming effect after weaning off CPB [35].…”
Section: Surgery Perfusion-related Risk Factorsmentioning
confidence: 99%
“…Cognitive impairment after cardiac surgery is driven by many preoperative, intraoperative, and postoperative risk factors. 51 Some modifiable factors include management of vital signs, [51][52][53] surgical manipulation, 54 sedation management, 55 and reduction of postoperative complications. 54 The interventions identified in this review primarily focused on maintaining adequate cerebral oxygenation and cognitive function but seldom on these other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 Decreased cerebral oxygenation is a risk factor for POCD and is associated with delirium and prolonged hospitalization, particularly in elderly patients. 26 , 27 Pneumoperitoneum and 30° Trendelenburg position may not affect cerebral oxygenation within 2 hours because of physiological compensation mechanisms. 28 However, cerebrovascular autoregulation gradually changes with prolonged pneumoperitoneum in the 45° Trendelenburg position.…”
Section: Discussionmentioning
confidence: 99%